Repair of Donor Site Defects After Forearm Free Flap Harvest With Dual Triangular Flaps and in Situ Small Full-thickness Skin Flaps. Issue 5 (July 2021) - Yao, Lin; Deng, Zhang; Guo, Mengmeng; Zeng, Wei; Yao, Lin
Abstract : Purposes: The aim of this study was to introduce a method for repairing donor site defects after harvesting forearm free flaps with dual triangular flaps combined with in situ small full-thickness skin flaps. Methods: Free forearm skin flaps were applied to repair defects after tumor resection in 25 patients with oral squamous cell carcinoma. Although forearm free flaps were prepared, dual triangular flaps and adjacent full-thickness skin flaps were designed and fabricated to repair donor site defects in situ. Results: Twenty-five cases of forearm donor site defects were successfully repaired with dual triangular flaps combined with in situ small full-thickness skin grafts. All adjacent full-thickness skin grafts used to close the donor site defect of the forearm survived, and the wound healed well without delayed wound rupture or serious complications at the donor site. The movement of the elbow and wrist joint on the side of the flap was normal, the blood supply in the palm was normal, and the skin color at the donor site of the forearm skin flap was similar to that of the surrounding tissue. There was no dent deformity or contracture deformity. Moreover, there was no significant difference in swelling and wrist movement between the adjacent forearm skin grafting group and the abdominal skin grafting group, but the former technique reduced the risk of scar infection and tendon exposure and greatly improved the esthetics of the surgical site on the forearm. Conclusions: Modified donor dual triangular flaps combined with adjacent full-thickness skin grafts can reduce the recovery time during and after surgery and avoid trauma at a third surgical site. This method is worthy of practical application in the preparation of forearm skin flaps for oral and maxillofacial surgery. Abstract : Supplemental Digital Content is available in the text